RIMAU Virtual Challenge 2021 raises funds of RM28,036 for the development of Mawaddah Residential College UMP - Siti Nurfarmy, Ibrahim (2021)
PEKAN, 11 October 2021 – RIMAU Virtual Challenge 2021 organised by Yayasan UMP managed to raise funds amounting to RM28,036 for the development of Mawaddah Residential College in Universiti Malaysia Pahang (UMP) campus in Pekan.